The Key Role of the Nonchelating Conformation of the Benzylidene Ligand on the Formation and Initiation of Hoveyda–Grubbs Metathesis Catalysts. Issue 29 (12th June 2015) - Bieszczad, Bartosz; Barbasiewicz, Michał
Abstract Experimental studies of Hoveyda–Grubbs metathesis catalysts reveal important consequences of substitution at the 6‐position of the chelating benzylidene ligand. The structural modification varies conformational preferences of the ligand that affects its exchange due to the interaction of the coordinating site with the ruthenium center. As a consequence, when typical S‐chelated systems are formed as kinetic trans‐Cl2 products, for 6‐substituted benzylidenes the preference is altered toward direct formation of thermodynamic cis‐Cl2 isomers. Activity data and reactions with tricyclohexylphosphine (PCy3) support also a similar scenario for O‐chelated complexes, which display fast trans‐Cl2⇄cis‐Cl2 equilibrium observed by NMR EXSY studies. The presented conformational model reveals that catalysts, which cannot adopt the optimal nonchelating conformation of benzylidene ligand, initiate through a high‐energy associative mechanism.